Muscarinic Acetylcholine Receptor Localization on Distinct Excitatory and Inhibitory Neurons Within the ACC and LPFC of the Rhesus Monkey - Tsolias, Alexandra; Medalla, Maria (Frontiers in Neural Circuits, 2022)
Acetylcholine (ACh) can act on pre- and post-synaptic muscarinic receptors (mAChR) in the cortex to influence a myriad of cognitive processes. Two functionally-distinct regions of the prefrontal cortex—the lateral prefrontal cortex (LPFC) and the anterior cingulate cortex (ACC) —are differentially innervated by ascending cholinergic pathways yet, the nature and organization of prefrontal-cholinergic circuitry in primates is not well understood. Using multi-channel immunohistochemical labeling and high-resolution microscopy, we found regional and laminar differences in the subcellular localization and the densities of excitatory and inhibitory subpopulations expressing m1 and m2 muscarinic receptors, the two predominant cortical mAChR subtypes, in the supragranular layers of LPFC and ACC in rhesus monkeys (Macaca mulatta). The subset of m1+/m2+ expressing SMI-32+ pyramidal neurons labeled in layer 3 (L3) was denser in LPFC than in ACC, while m1+/m2+ SMI-32+ neurons co-expressing the calcium binding protein, calbindin (CB) was greater in ACC. Further, we found between-area differences in laminar m1+ dendritic expression, and m2+ presynaptic localization on cortico-cortical (VGLUT1+) and sub-cortical inputs (VGLUT2+), suggesting differential cholinergic modulation of top-down versus bottom-up inputs in the two areas. While almost all inhibitory interneurons—identified by their expression of parvalbumin (PV+), CB+ and calretinin (CR+)—expressed m1+, the localization of m2+ differed by subtype and area. The ACC exhibited a greater proportion of m2+ inhibitory neurons compared to the LPFC and had a greater density of presynaptic m2+ localized on inhibitory (VGAT+) inputs targeting proximal somatodendritic compartments and axon initial segments of L3 pyramidal neurons. These data suggest a greater capacity for m2+-mediated cholinergic suppression of inhibition in the ACC compared to the LPFC. The anatomical localization of muscarinic receptors on ACC and LPFC micro-circuits shown here contributes to our understanding of diverse cholinergic neuromodulation of functionally-distinct prefrontal areas involved in goal-directed behavior, and how these interactions maybe be disrupted in neuropsychiatric and neurological conditions.